2019
DOI: 10.1016/j.jad.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Directionality of change in obsessive compulsive disorder (OCD) and suicidal ideation over six years in a naturalistic clinical sample✰

Abstract: Background: Obsessive compulsive disorder (OCD) is associated with elevated suicide risk, but the directionality of the association between OCD severity and suicidal ideation has not been established, which was the goal of this study. Methods: Participants (n = 325) were adults with either a current or past diagnosis of Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM-IV) OCD who were assessed annually for suicidal ideation and OCD symptom severity for six years. Cross-lagged panel analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…Obsessive-compulsive disorder (OCD) is a chronic illness characterized by compulsive urges resembling avoidance of perceived danger 1 . Behaviorally, OCD is treated with exposure-with-response prevention (ERP) therapy, in which patients are coached to refrain from carrying out compulsions in response to environmental triggers, with the intention of extinguishing those behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Obsessive-compulsive disorder (OCD) is a chronic illness characterized by compulsive urges resembling avoidance of perceived danger 1 . Behaviorally, OCD is treated with exposure-with-response prevention (ERP) therapy, in which patients are coached to refrain from carrying out compulsions in response to environmental triggers, with the intention of extinguishing those behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Kamath et al 9 have found higher YBOCS obsession subscale scores in patients with OCD who had suicidal ideation and previous suicide attempts. Brown et al 3 have determined a one-way relationship between OCD symptoms and suicidal ideation in a 6-year follow-up study. According to Brown et al, 3 as the severity of OCD symptoms increased, the severity of suicidal ideation increased, but suicidal ideation did not affect OCD symptoms over the years.…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al 3 have determined a one-way relationship between OCD symptoms and suicidal ideation in a 6-year follow-up study. According to Brown et al, 3 as the severity of OCD symptoms increased, the severity of suicidal ideation increased, but suicidal ideation did not affect OCD symptoms over the years. We found higher scores in avoidance, indecisiveness, global severity, and total obsession subdimensions of YBOCS, and also higher BSIS, PS, and total YBOCS scores in OCD patients with a history of previous suicide attempts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations